Groundswell Africa : Internal Climate Migration in the Lake Victoria Basin Countries - Rigaud, Kanta Kumari; de Sherbinin, Alex; Jones, Bryan; Adamo, Susana; Maleki, David; Arora, Anmol; Casals Fernandez, Anna Taeko; Chai-Onn, Tricia; Mills, Briar (World Bank, Washington, DC, 2021)
This report, as part of the Groundswell Africa series, reaffirms the potency for climate change to drive internal migration in the Lake Victoria Basin. The results described in this report are based on the application of an enhanced version of the pioneering Groundswell model with a more granular analysis and additional features better placed to inform policy dialogue and action. Without concrete climate and development action, the five Lake Victoria Basin countries could see between 16.6 and 38.5 million people moving within their countries in response to water scarcity, declines in crop productivity and ecosystem productivity, and sea level rise, augmented by storm surge. The analysis also includes consideration of nonclimate factors. The countries will see an emergence of climate in- and climate out-migration hotspots, as early as 2030, but with continued spread and intensification by 2050. Concrete climate and development action could reduce the scale of internal climate migration across the Basin countries by 30 percent. No country in the Lake Victoria Basin is immune to internal climate migration, but there are differences among countries depending on their demographic, economic, and climate trends. Tanzania and Uganda are projected to have the highest numbers of internal climate migrants by 2050, reaching a high of 16.6 million and 12.0 million, respectively, under the pessimistic scenario (which combines high emissions with unequal development pathways). This will be followed by Kenya (7.6 million), Rwanda (1.2 million), and Burundi (1.0 million). This report presents the Migration and Climate-informed Solutions (MACS) framework that brings together domains of action, buttressed by core policy areas, to reduce the scale of climate-induced migration, usher in social and economic transformations, and reduce vulnerabilities. This anticipatory approach will ensure that the countries in the Basin are braced not just for the challenges but have the readiness to harness the opportunities of internal climate migration. The urgency to reduce greenhouse gases remains paramount to reduce the scale of climate impacts that could otherwise drive increased levels of climate migration - the window of opportunity is rapidly narrowing.